2004
DOI: 10.1196/annals.1306.017
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Iron in the Pathogenesis of Parkinson's Disease

Abstract: Investigations that revealed increased levels of iron in postmortem brains from patients with Parkinson's disease (PD) as compared to those from individuals not suffering from neurological disorders are reported. The chemical natures in which iron predominates in the brain and the relevance of neuromelanin for neuronal iron binding are discussed. Major findings have been that iron levels increase with the severity of neuropathological changes in PD, presumably due to increased transport through the blood-brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
153
1
11

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(167 citation statements)
references
References 119 publications
2
153
1
11
Order By: Relevance
“…Abnormally high levels of iron seen at autopsy are associated with nigral degeneration in PD and increase with the severity of neuropathologic changes (9,221). Although increased iron could signal a primary role of oxidative stress in PD pathology, iron overload could alternatively be a consequence of sequestration by eosinophilic protein aggregates.…”
Section: Role Of Oxidative Stress In the Pathogenesis Of Pd And Modelmentioning
confidence: 99%
“…Abnormally high levels of iron seen at autopsy are associated with nigral degeneration in PD and increase with the severity of neuropathologic changes (9,221). Although increased iron could signal a primary role of oxidative stress in PD pathology, iron overload could alternatively be a consequence of sequestration by eosinophilic protein aggregates.…”
Section: Role Of Oxidative Stress In the Pathogenesis Of Pd And Modelmentioning
confidence: 99%
“…However, postmortem evidence of increased iron content in the SN of parkinsonian brain [7] has suggested that the generation of reactive oxygen species, possibly facilitated by iron, may be responsible for cellular damage and the subsequent cell death. Others have suggested that iron levels increase with the progression of PD [8] .…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence suggests that iron accumulation plays a key role in the etiology and pathology of neurodegenerative diseases, such as Parkinson's disease (Gotz et al, 2004;Berg and Hochstrasser, 2006). However, the underlying mechanisms of iron accumulation have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…However, excess iron can generate highly reactive hydroxyl radicals ( OH) by the Fenton reaction (Stohs and Bagchi, 1995), which can damage proteins, lipids and DNA. Recently many literatures have confirmed that iron plays a key role in Parkinson's disease (PD) and other neurodegenerative diseases (Gotz et al, 2004;Wang et al, 2004Wang et al, , 2007Youdim et al, 2004;Berg and Hochstrasser, 2006;Jiang et al, 2006Jiang et al, , 2007. Increased iron content was found in the substantia nigra pars compacta (SNpc) of parkinsonian brains (Atasoy et al, 2004;Gerlach et al, 2006).…”
Section: Introductionmentioning
confidence: 99%